Pengaruh Good Corporate Governance pada Kinerja LPD dengan Budaya Organisasi Berorientasi Tim sebagai Variabel Mediasi - Darmayanti, Ni Putu Gita; Dwi Ratnadi, Ni Made; Aryista Dewi, Ayu; Wirawan Yasa, Gerianta (E-Jurnal Akuntansi; Vol 30 No 10 (2020), 2020)
This research was aims to obtain to empirical evidence of the influence of GCG on the performance of LPD, the effect of GCG on team-oriented organizational culture, the influence of team-oriented organizational culture on LPD performance, examine the culture of team-oriented organizations as mediating the relationship between GCG on LPD performance. The research population was 50 LPD in Penebel, Tabanan. The sample was determined by the nonprobability sampling method with a purposive sampling technique, obtained as many as 25 LPD. The data are analyzed using path analysis. The analysis shows that GCG has a positive effect on LPD performance. GCG has a positive effect on team-oriented organizational culture. Team-oriented organizational culture has a positive effect on LPD performance. Team-oriented organizational culture mediates a part of the influence of GCG on LPD performance. Keywords: Good Corporate Governance; Team-Oriented Organizational Culture; Performance of Lembaga Perkreditan Desa.